Financial Development and Economic Growth in Latin America: Is Schumpeter Right? - Manoel Bittencourt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In this paper we investigate the role of financial development, or more widespread access to all sorts of finance, in generating economic growth in four Latin American countries between 1980 and 2007. The results, based on panel time-series data and analysis, confirm the Schumpeterian prediction which suggests that finance authorises the entrepreneur to invest in productive activities, and therefore to promote economic growth. Furthermore, given the characteristics of the sample of countries chosen, we highlight not only the importance of a more open, competitive and therefore active financial sector in channelling financial resources to entrepreneurs, but also the relevance of macroeconomic stability (in terms of low inflation rates), and all the institutional framework that it encompasses (central bank independence and fiscal responsibility laws), as a necessary pre-condition for financial development, and consequently for sustained growth and prosperity in the region.
Keywords: E31; N16; O11; O54; 330; Finance; growth; Latin America